ROKAT BELIUNEH: ANTARA BUDAYA DAN SYARIAT ISLAM (Studi Analisis Budaya di Desa Ganding Sumenep Madura) - Abdur Rakib (Universitas Nurul Jadid, 2022)
The law does not come in a social vacuum, in fact the law comes when there is social activity. Consequently, every social treatment definitely requires certain laws and rules. Meanwhile, religion exists because it functions as a guide to good and values and keeps away from substantial evil. Therefore, every culture is believed to allow for two opposite things, namely wrong culture and religiously right culture.In considering the Al-Quran and Hadith of the Prophet, Muslims believe that the death of a person is an event that can cut off his good deeds (including bad deeds) except through three things, so that every time someone dies in the village of Ganding there is a habit of praying and giving alms for his family. died with the aim of alleviating the burden of the sins of the deceased and providing good benefits through the Rokat Beliuneh ritual.However, Beliuneh's rokat culture does not have clear adequate references and arguments in both the Koran and the hadits of the Prophet and even the opinions of the scholars, from this it requires proper thinking to combine cultural reality and the substance of religious values if it does not have fatal consequences in the realm of I'tiqadyKeywords : Beliuneh's Rokat, Culture, Islamic Law